Roux-en-Y Gastric Bypass in Obese Diabetic Rats Promotes Autophagy to Improve Lipid Metabolism through mTOR/p70S6K Signaling Pathway - Nanxi Ma; Rui Ma; Kaixin Tang; Xuesong Li; Bing He (Journal of Diabetes Research)
Purpose. To investigate the effects of Roux-en-Y gastric bypass (RYGB) surgery on markers of liver mitochondrial dynamics and find new therapeutic basis on obese type 2 diabetes mellitus (T2DM) patients. Materials and Methods. Thirty-two rats were divided into nondiabetic group, diabetic group, sham group, and RYGB group. The Dual-energy X-ray absorptiometry (DEXA) was used to detect short-term curriculum vitae for rat body component and fat and lean mass. Hepatic lipid content and triglyceride levels were detected by Oil Red O staining. Western blotting was used to examine autophagy and mammalian target of rapamycin/P70S6 kinase (mTOR/p70S6K) pathway-related proteins. The carbon dioxide production from the oxidation of [14C] oleate was measured. Plasma glucose was measured by glucose oxidase assay. The insulin and C-peptide were detected. Triacylglyceride (TG) and free fat acid (FFA) in plasma were determined by enzymatic colorimetric assays. Results. RYGB improved metabolic parameters and enhanced plasma GLP-1 level, ameliorated the lipopexia, and increased insulin sensitivity in the liver; RYGB promoted the hepatic autophagy and inhibited the mTOR/p70S6K signaling pathway. GLP-1 reduced fat load and increased fatty acid β-oxidation by activated autophagy to regulate the hepatic lipid pathway through mTOR/p70S6K signaling pathway. Conclusions. RYGB may reduce liver lipid toxicity and improve insulin sensitivity through activating the hepatic fat hydrolysis pathway and inhibiting the liver fat synthesis pathway. However, the transport pathway of liver fat does not play a key role.